2014
DOI: 10.1371/journal.pone.0109082
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Dependence of Insulin Granule Movement Dynamics in INS-1 Beta-Cells in Response to Glucose

Abstract: For pancreatic β-cells to secrete insulin in response to elevated blood glucose, insulin granules retained within the subplasmalemmal space must be transported to sites of secretion on the plasma membrane. Using a combination of super-resolution STORM imaging and live cell TIRF microscopy we investigate how the organization and dynamics of the actin and microtubule cytoskeletons in INS-1 β-cells contribute to this process. GFP-labeled insulin granules display 3 different modes of motion (stationary, diffusive-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
110
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(125 citation statements)
references
References 61 publications
13
110
2
Order By: Relevance
“…This model appears plausible, because in many cell types long-distance secretory membrane trafficking utilizes MT tracks, which extend radially from the cell center to the periphery. However, while MT-dependent motors indeed continuously translocate insulin granules along MTs (Heaslip et al, 2014; Varadi et al, 2002; Varadi et al, 2003), the radial MT tracks reported in pancreatic cells by Boyd et al, was not confirmed by later studies: in β-cell lines MTs form a complex nondirectional mesh (Heaslip et al, 2014; Varadi et al, 2002), poising challenges for directional cargo transport. Furthermore, the importance of MTs for GSIS has been questioned by recent experimental (Mourad et al, 2011) and computational (Tabei et al, 2013) studies, which showed that MTs are not required for GSIS and that random, diffusion-like movement rather than directional transport accounts for vesicular delivery in β cells, respectively.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This model appears plausible, because in many cell types long-distance secretory membrane trafficking utilizes MT tracks, which extend radially from the cell center to the periphery. However, while MT-dependent motors indeed continuously translocate insulin granules along MTs (Heaslip et al, 2014; Varadi et al, 2002; Varadi et al, 2003), the radial MT tracks reported in pancreatic cells by Boyd et al, was not confirmed by later studies: in β-cell lines MTs form a complex nondirectional mesh (Heaslip et al, 2014; Varadi et al, 2002), poising challenges for directional cargo transport. Furthermore, the importance of MTs for GSIS has been questioned by recent experimental (Mourad et al, 2011) and computational (Tabei et al, 2013) studies, which showed that MTs are not required for GSIS and that random, diffusion-like movement rather than directional transport accounts for vesicular delivery in β cells, respectively.…”
Section: Introductionmentioning
confidence: 92%
“…MT-dependent insulin granule transport has been best studied utilizing total internal reflection fluorescence (TIRF) microscopy in β -cell culture models (Heaslip et al, 2014; Hoboth et al, 2015; Varadi et al, 2003). It has become clear that recently generated (“young”) insulin granules, competent of release, are moved along the cell membrane in a MT-dependent manner (Hoboth et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In primary ␤-cells, the actin mesh impedes insulin granule trafficking, and F-actin depolymerization contributes to increased glucosestimulated insulin secretion (22,53). This is in contrast to poorly granulated ␤-cell lines such as INS-1, where the actin network does not hinder granule trafficking and its depolymerization does not significantly increase insulin secretion (18,34,55). These divergent effects of actin mesh on secretion could help explain why transcellular CADM1 interactions decrease insulin secretion by primary ␤-cells while increasing secretion by INS-1 cells.…”
Section: Cadm Expression In Human and Rat Isletsmentioning
confidence: 98%
“…To understand the mechanism of obesity-mediated insulin resistance and impairment in insulin secretion it' s better to first review the mechanisms of glucose stimulated insulin In response to increased blood glucose levels, insulin is released from dense core pancreatic islet ~-cells in a biphasic manner (Heaslip, Nelson et al 2014). The first phase results in a rapid robust spike of insulin release due to rapid fusion of granules that are pre-docked at the plasma membrane.…”
Section: General Introduction To Lipotoxicitymentioning
confidence: 99%
“…These pre-docked granules are referred as the 'readily releasable pool' (RRP) (Wang and Thurmond 2009). Second, prolonged release of insulin occurs in response to sustained stimulation and requires recruitment of granules from the storage pool to the plasma membrane (Heaslip, Nelson et al 2014). Docking and fusion of insulin granules is mediated by a group of proteins termed as soluble Nethylmaleimide sensitive factor attachment receptor (SNARE) proteins.…”
Section: General Introduction To Lipotoxicitymentioning
confidence: 99%